Synthesis and characterization of 9.5/65/35 PLZT prepared from the polymeric precursors - Stojanovic, B. D.; Zaghete, M. A.; Foschini, C. R.; Cavalheiro, A. A.; Paiva-Santos, C. O.; Cilense, M.; Longo, Elson [UNESP] (Elsevier B.V., 2001)
The 9.5/65/35 PLZT was prepared from the polymeric precursors (the Pechini and partial oxalate process) and by sintering in two stages in an oxygen atmosphere. After thermal treatment at 400 degreesC, the powders were calcinated and sintered at 1200 degreesC with slow heating and cooling rates. The second stage of sintering consisted of hot pressing at the same temperature in oxygen atmosphere. After calcination of PLZT powders obtained by both methods, as well as after sintering of PLZT obtained by Pechini process, the paraelectric cubic phase was formed. After sintering of PLZT obtained by partial oxalate procedure, small tetragonality of crystal structure was observed. After hot pressing PLZT was pseudocubic. SEM microstructural analyses were carried out of the sintering and hot pressed samples and indicated the small grain size less than 2 mum. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: PLZT; powder preparation; polymeric precursors; hot pressing; X-ray; SEM